Exposure of juvenile Chinook salmon to effluent from a large urban wastewater treatment plant. Part 2. Metabolomic profiling - James P. Meador; Suzanne C. Ball; C. Andrew James; Jenifer K. McIntyre (Aquaculture and Fisheries, 2024)
Targeted metabolomic analysis was conducted on juvenile Chinook salmon exposed for 10 days to wastewater effluent (WWE) from a large urban treatment plant. Exposures included five dilutions of WWE (20%, 5.3%, 1.4%, 0.4%, and 0.1%) and a control with 7 replicates per treatment. Liver was extracted from fish and analyzed via liquid chromatography – mass spectrometry (LC-MS) for 361 endogenous metabolites, of which 185 were detected. Control-versus-treatment comparisons identified several metabolites that were associated with altered biochemical pathways observed for all treatments, including several that are important for energy generation and utilization. These altered pathways are crucial for fish health and may be an early indicator of potential adverse effects on growth, reproduction, behavior, and immune function. Juvenile ocean-type Chinook salmon spend several days to weeks in the nearshore estuary where they may encounter high concentrations of WWE contaminants. They are exposed to a wide range of potent pharmaceuticals, personal care products, and industrial compounds from WWE that have the potential to affect physiological homeostasis and disrupt their normal life cycle.